The Question ofTranslating Literature: Reading and Translation of Two Poems by Paul Éluard - Fernandez Cozman, Camilo (2004)
Literary translation means transferring information from an originallanguage into another, a complex task for a translator who has topreviously make a textual and intertextual analysis of, in this case, twopoems, in order to build a version in the second language. Then, bothworks are put across for intertextual comparison.